Acute Interstitial Nephritis Proteinuria and Herpes Simplex Virus Hepatitis in Pregnancy Mimic HELLP Syndrome (Hemolysis, Elevated Liver Enzymes, Low Platelets) - Wendy M. White; Diana Tran; Vesna D. Garovic; Brian Brost (Thieme Medical Publishers, Inc., 2011)
Elevated transaminases, hemolysis, and thrombocytopenia in pregnancy are most often caused by a preeclampsia variant-HELLP syndrome (hemolysis, elevated liver enzymes, low platelets). In atypical cases, it is important to consider other causes, such as herpes simplex virus (HSV) hepatitis. Acute interstitial nephritis (AIN)-induced proteinuria can make distinguishing HELLP from its mimics more difficult. A 43-year-old G4P3 gestational carrier at 28 weeks had abnormal laboratory findings consistent with HELLP, including proteinuria. However, she was normotensive and febrile, prompting an investigation into other possible causes of her signs and symptoms. She ultimately was diagnosed with disseminated HSV infection, started on definitive therapy, and allowed to continue her pregnancy to term. The proteinuria was attributed to AIN. AIN can cause proteinuria in the critically ill pregnant patient. When mimics of HELLP syndrome, such as disseminated HSV infection, are the cause of critical illness, the presence of AIN-induced proteinuria may falsely implicate a hypertensive disorder of pregnancy, resulting in iatrogenic premature delivery of the fetus and failure to initiate definitive potential lifesaving treatment.